Heat stress sensitizes zebrafish embryos to neurological and cardiac toxicity - Haapanen-Saaristo, Anna-Mari; Virtanen, Noora; Tcarenkova, Elena; Vaparanta, Katri; Ampuja, Minna; Vehniainen, Eeva-Riikka; Paatero, Ilkka (Elsevier BV, 2025)
Global warming increases the risk of dangerous heat waves, which may have deleterious effects on humans and wildlife. Here, we have utilized zebrafish embryos as a model to analyze heat stress and effect of chemical compounds on responses to heat stress. The temperature adaptation limit of zebrafish embryos was 37 degree celsius in behavioural test and 38 degree celsius in cardiac test. Polyaromatic hydrocarbon phenanthrene completely blocked the behavioural adaptation to heat stress. Interestingly, the cardiotoxic effects of lapatinib, phenanthrene and paclitaxel were induced by heat stress. Taken together, our data indicates that motility and cardiac function of zebrafish embryos can be utilized as a model to analyze modulatory effects of compounds on heat stress.